Caracterização mecânica e dinâmica dos óxidos constituintes do cimento portland e do silicato de cálcio hidratado através da teoria do funcional da densidade - Andrade, Jefferson Maul de (2024)
In this study, the main focus is the mechanical and dynamical characterization of cementitious components, using atomistic models to understand the properties of this complex system. Density Functional Theory (DFT) was employed as a tool for atomic-level analysis, allowing an in-depth investigation of the structural and electronic properties of the materials, despite the high computational cost associated with such complex systems. Parallel computing was essential for performing the calculations, as it enabled multiple simulations to be executed simultaneously on different processors. This approach significantly reduced the time required to obtain results, mitigating the limitations imposed by computational time. Thus, it was possible to study the dynamic and mechanical aspects of the main oxides constituting the clinker, which is the primary component of Portland cement: C3S, C2S, C3A, and C4AF, in addition to an initial study of clinker hydration, resulting in the formation of calcium silicate hydrate (C-S-H). The main results include the generation of Raman spectra and the analysis of the evolution of the elastic tensor and the associated mechanical properties under different external stimuli (pressure, strain, and temperature). In the study of clinker, special attention was given to the evaluation of the dynamic and mechanical stability of the many proposed polymorphic forms of the most abundant oxide: C3S. Specifically, five different crystalline models of C3S were analyzed, of which only two were found to be dynamically stable. The mechanical response of C3S was further examined as a function of temperature through a quasi-harmonic description. For C-S-H, a model based on the mineral tobermorite was adopted and considered appropriate, given the high agreement between the theoretical and experimental spectra. Different Ca/Si ratios were explored to find the one that best matched the experimental spectrum of C-S-H. The use of Qn species (related to the formation of bridges between oxygen atoms of silicon tetrahedra) in the evaluation of the bands was essential for the confirmation of the models. Although the individual spectra at different Ca/Si ratios showed only partial agreement with the experimental spectrum of C-S-H, the combination of the calculated Raman spectra resulted in a "synthetic" spectrum with remarkable agreement with the experimental spectrum. This result is significant, especially considering the complexities of including water molecules in the structure, which could challenge the harmonic approximation used. Thus, the presented models prove to be capable of reliably reproducing experimental data and have the potential to predict new properties, thereby can be used to support decisions and technological advances related to sustainable development.